THE INFLUENCE OF THE TGT (TEAMS GAMES TOURNAMENT) LEARNING MODEL ON BASKETBALL CHEST PASS LEARNING OUTCOMES IN CLASS XI STUDENTS AT XAVERIUS VOCATIONAL SCHOOL PALEMBANG - Ridwan, M.; Cicilia Kristina, Putri Cicilia Kristina; Kumbara, Hengki (Indonesia Sport Journal, 2023)
Based on the research results, it was found that there was an influence of the TGT (Teaching Games Tournament) model on the basketball chest pass learning outcomes of class XI students at Xaverius Vocational School, Palembang. This is proven by research findings which show that tcount is greater than ttable (2.413 > 1.70). The influence of games on chest pass learning outcomes shows that the quality of learning through games has really been proven to be significant. Through continuous and consistent learning, students experience good improvement in making chess passes. Based on the results of the data analysis that has been described, this research concludes that there is an influence of the TGT (Teaching Games Tournament) model on the basketball chess pass learning outcomes of class XI students at Xaverius Vocational School, Palembang. This is proven by research findings which show that tcount is greater than ttable (2.413 > 1.70).